O Ciberjeca - Ferreira, André Nóbrega Dias (2009)
This research has the subject the passage of popular comedy to a digital media using, as main focus, one comedian: Mazzaropi. It is not the simple digitalization of pictures, movies and another data, but also share new technologies with cultural memory, after of the recovery of data got from the prospection of spare materials, after the death of the comedian. The problem of the localization, of lost material and new ones, was the central ponit of the field research. Locate people who no one knows and get theirs speeach, was started from the personal history of the artist, and the cities where he was in the state of São Paulo, and others, place where there was material existece possibility. Once got, the material was used to built an envirolment whose the especific approach could get the comic behaveour as a condition of the navigation and creation of the inferface, based in the humoristic transposition into a interctive multimedia environment, doing a prototype. The problens concerned to the archiving made dificult the recovery of the artist s live memory. In the transposition to a modern media, it is also recovery the memory of a group, belonging to the caipira univers, who was his great movie audience. Rebuilt this memory, get an act of colect the material, share then to everyone, at least those who has computer access, to put togeter a imaginary of artistics and cultural praticies lost. The prototype wil beyond of the release of material. As a prize, it will operate to the users who won the obstacles of the envoronment, regulated for the agency based in the artist s humoristic actitude. In this momento, will happen the visualization of part of a circus performance remade from another one reccorded, recovering, inpart, the spacial tatility